Faktor Risiko Persalinan Seksio Sesarea - Putri, Bunga Artha Meivia; Rosyidah, Rafhani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the risk factors for cesarean section delivery. The method used is an analytic observational study with a case-control design, namely comparing the case group and the control group. The results showed that the risk factor associated with cesarean section delivery was the age of the mother (ρ=0.004; OR=0.368; 95% CI=0.191-0.710). Old labor with values (ρ=0.019; OR=0.206; 95%CI95%CI=0.57-0.748). Placental condition with values (ρ=0.023; OR=9.828; 95% CI=1.220-79.166). Preeclampsia with a value (ρ=0.004; OR=3.667; 95% CI=1.554-8.653). History of caesarean section delivery (ρ=0.000; OR=8.556; 95% CI=3.736-19.591). Risk factors for caesarean section delivery that have a relationship are maternal age, prolonged labor, placental conditions, preeclampsia, and history of caesarean section delivery. while the risk factors that have no relationship are pelvic conditions, abnormal location, macrosomia, number of fetuses, fetal distress, premature rupture of membranes, preterm labor, and preterm labor. In conclusion, knowing the factors of caesarean section is expected to reduce the incidence of cesarean section for the welfare of the mother and fetus by promoting health and providing health services according to the needs of the mother and fetus from an early age so as not to have complications in labor and pregnancy. Keywords: Risk Factors, Childbirth, Caesarean Section